The Potential Role of Neurophysiology in the Management of Multiple Sclerosis-Related Fatigue - Capone, Fioravante; Motolese, Francesco; Falato, Emma; Rossi, Mariagrazia; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2020)
Fatigue is a very common symptom among people with multiple sclerosis (MS) but its management in clinical practice is limited by the lack of clear evidence about the pathogenic mechanisms, objective tools for diagnosis, and effective pharmacological treatments. In this scenario, neurophysiology could play a decisive role thanks to its ability to provide objective measures and to explore peripheral and central structures of the nervous system. Hereby, we review and discuss current evidence about the potential role of neurophysiology in the management of MS-related fatigue. In the first part, we describe the use of neurophysiological techniques for exploring pathogenic mechanisms of fatigue. In the second part, we review the potential application of neurophysiology for monitoring response to pharmacological therapies. Finally, we show data about therapeutic implications of neurophysiological techniques based on non-invasive brain stimulation.